PENGEMBANGAN MEDIA INTERAKTIF BERBASIS WORDWALL TERHADAP HASIL BELAJAR IPA SISWA - Septianih, Nabilah; Nuraeni, Yeni; Nurfadhillah, Septi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
The science learning process plays an important role in actively involving students in the learning process. This can be facilitated by developing a Wordwall "Open the Box" media on the Human Respiratory System material. This research is an R&D study that refers to the Borg and Gall development model. The research subjects consisted of 30 fifth-grade students in a trial at SDN Panunggangan 8, Tangerang City. The results of the study showed that the validity percentage of the media was 81.3%, the material experts' assessment was 85.3%, and the fifth-grade teachers' assessment was 100%, all indicating valid criteria. The practicality percentage from the student response questionnaire was 4.1 in a large-scale trial with the category of "good/feasible". Based on the development research conducted, students were very enthusiastic about using the Wordwall "Open the Box" media, and it can be concluded that the Wordwall "Open the Box" media on the Human Respiratory System material is feasible to be used by fifth-grade elementary school students to improve learning outcomes.